Deteksi Dini Stunting dengan Pengukuran Tinggi Badan dan Berat Badan dalam Menentukan Status Gizi di Kelurahan Alai Parak Kopi Wilayah Kerja Puskesmas Alai - Permata Sari, Putri; Hasanalita; Wikarya, Rionitara; Rita Aninora, Novia; Satria, Epi (PADMA, 2024)
Stunting occurs in the first 1000 days of life (HPK). The risk of stunting is that there are obstacles to physical growth and vulnerability to disease in children and causes delays in cognitive development which affects the level of intelligence. Apart from that, stunting also affects children's productivity in the future. The results of the 2018 Basic Health Research (Riskesdas) show a decline The prevalence of stunting at the national level was 6.4% over a 5 year period, namely from 37.2% (2013) to 30.8% (2018). Meanwhile, for toddlers with normal status, there was an increase from 48.6% (2013) to 57.8% (2018). West Sumatra Province itself has a stunting prevalence rate in 2021 of 23.3%, lower than the national figure. The prevalence of underweight among children under five in the Mentawai Islands district in 2022 will reach 13.8% from the target of 14.5%. Based on data obtained in Sirisurak Hamlet, Saibi Samukop Village, there were 58 children in August 2024, and 17 children experienced malnutrition. Purpose: The main objective of this community service is to help government programs in this case in the Sirisurak Hamlet area, Saibi Samukop Village, where there are 17 people with malnutrition. Apart from that, it is hoped that this counseling can increase the knowledge of mothers of toddlers about stunting. Method: Stages of community service activities include: 1) Assessing and identifying problems, 2) Determining targets, 3) Coordinating with the village head, midwife and posyandu cadres. 4) Implementation of activities. Result: The results obtained were that of the 58 children under five who carried out their weight and measured their height, there was 1 (1.7%) child under five with very short status, 8 (13.8%) children under five with short status, 44 (75.9%) with normal status, and 5 (8.6%) children under five with high status. From these results, instructors carried out outreach related to stunting in children under five. Conclusion: The results of community service in the form of stunting education to mothers of toddlers are very useful for increasing the knowledge of mothers of toddlers regarding stunting. Suggestion: it is necessary for health workers to make house-to-house visits to detect early incidents of malnutrition which can result in stunting.